2017
DOI: 10.12691/jfnr-6-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food Proteins on Sensory and Physico-Chemical Properties of Emulsified Pork Meatballs

Abstract: Emulsified pork meatballs (Kung-Yuan or meatballs) are common emulsified meat products in Chinese cultures and are widely popular among Taiwanese and Chinese consumers. In recent years, the concept of clean labels has become prominent, and consumers have started to demand products without artificial additives. In this study, we investigated the effects of food proteins-soy protein, sodium caseinate, whey protein, egg albumen powder, and skim milk powder on the texture and sensory acceptability of phosphate-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Petkova et al [ 24 ] suggested that the antimicrobial activity of inulin acetates reveals a new aspect of their potential application against some plant and food-borne pathogens. Yeung et al [ 25 ] reported that the TVCs of the emulsified pork meatballs with the 2% whey protein and 6% isolated soy protein treatments were lower than that of the positive control group. Yim et al [ 26 ] stated that total plate bacteria and Pseudomonas counts of sausages were not significantly affected by fat level.…”
Section: Resultsmentioning
confidence: 99%
“…Petkova et al [ 24 ] suggested that the antimicrobial activity of inulin acetates reveals a new aspect of their potential application against some plant and food-borne pathogens. Yeung et al [ 25 ] reported that the TVCs of the emulsified pork meatballs with the 2% whey protein and 6% isolated soy protein treatments were lower than that of the positive control group. Yim et al [ 26 ] stated that total plate bacteria and Pseudomonas counts of sausages were not significantly affected by fat level.…”
Section: Resultsmentioning
confidence: 99%
“…Authors such as Aripin et al [75] reported the preparation of meatballs with chicken and duck meat in various concentrations, to obtain low protein content (from 5.88-10.45%). Yeung and Huang [76] prepared pork meatballs with the incorporation of different additives, to obtain elevated protein levels (from 15.74-16.04%).…”
Section: Nutritional Composition Of Selected Meatballs (Ai)mentioning
confidence: 99%
“…Processed meat products can be defined as products that have been modified through processes such as smoking, salting, and curing to improve quality and shelf life; they consist of a different range of meat products depending on the processing technique applied and nutritional composition (i.e., fat and salt content) of these products (Shan et al., 2017). As consumers demand convenience and quality (i.e., taste, flavor, texture, and nutritional profile), that is why processed meat products are trendy, being consumed by many individuals in the developed world, and this trend is gradually increasing (Ağar et al., 2016; Shan et al., 2017; Yeung & Huang, 2018; Fernández‐López et al., 2021; Antonini et al., 2020; Lu et al., 2021; Diao et al., 2020; Domínguez, Munekata, et al., 2020; Skałecki et al., 2021; Domínguez, Bohrer, et al., 2021). Consumers demand healthier processed meat products in terms of reduced salt and fat content than other ingredients.…”
Section: Processed Meat Productsmentioning
confidence: 99%